The Notch signal mediates macrophage polarization by regulating miR-125a/miR-99b expression. Issue 1 (4th December 2019) - Li, Qian; He, Xia; Yu, Qiao; Wu, Yuan; Du, Mingyu; Chen, Jing; Peng, Fanyu; Zhang, Wenjun; Chen, Jie; Wang, Yan; Chen, Hanbo; Wang, Hairong; et al.
Abstract: We aimed to explore the mediating role of Notch signal in macrophage polarization. This signal was knocked out from macrophages of Lyz2 cre and RBP-J flox mice. Bone marrow-derived macrophages (BMDMs) were isolated and polarized. The expressions of polarization markers in BMDMs 24 h after transfection were detected by qPCR. After Notch knockout, the expressions of M1 markers decreased but those of M2 markers increased significantly. MiR-125a/miR-99b and Spaca6 were highly and lowly expressed upon M1 and M2 polarizations, respectively. The expressions of experimental group were significantly lower than those of control group. Overexpression of miR-125a significantly promoted the expressions of M1 markers, whereas inhibited those of M2 markers. NO release in the culture supernatant of miR-125a overexpression group significantly exceeded that of control group. Transfection with miR-125a inhibitor significantly down-regulated IL-12 expression but up-regulated MR expression in BMDMs. The supernatant secreted by M1 macrophages significantly facilitated BS524 cell apoptosis, which was enhanced after miR-125a overexpression. The TNF-α expression of miR-99b overexpression group increased whereas that of MR decreased significantly. The miR-125a/miR-99b cluster contained an RBP-J specific recognition site in the first intron of initial transcript. The Notch signalling pathway promoted macrophage polarization into M1 phenotype by up-regulating miR-125a/miR-99b expression.